CLASSICAL STRATEGIES OF TRANSNATIONAL COMPANIES FROM EMERGING COUNTRIES - ELENA MARGULESCU; SERGHEI MARGULESCU (Challenges of the Knowledge Society)
The analysis of strategies adopted in the last 10-15 years by companies in emerging countries that have managed to reach the status of global companies, enables us to appreciate that, in a first stage, emerging companies have followed the "normal" principles of corporate strategies that have lead Western companies to a multinational or a transnational status. But more important is what happened in the second stage, namely that many emerging companies were able to overcome the classical principles and strategies and to develop new business models, such as the integration of "functions" resulted from the global value chain restructuring, based on the new "functional" specialization in manufacturing and services, the building up of global networks of suppliers or the reverse outsourcing. However, the range of strategies implemented by emerging companies in their efforts to become global players comprise also “classical” strategies such as the global brand development, the global development and supply of niche products, the non-organic growth or the strategy of geographical adjustment of business flows on South-South and South-North directions.